From Doubt to Digital Presence: Insecurity and Self-Confidence on Intentions to Use Social Media in Students - Lisa Nur Saidah; Sigit Hariyadi (STAI Hubbulwathan Duri, 2023)
This study seeks to analyse how feelings of uncertainty and self-confidence impact students' inclination to utilise social media. This research is quantitative. The study's population consisted of students. The sampling employed the cluster random sampling method with a total sample size of 376 students. The data collection technique uses an insecure scale developed from the theory of Kim Kim (2005, 2017) and Ting-Toomey (2005, 2015) with a validity of 0.314 – 0.884 and reliability α = 0.976. The self-confidence scale was developed from Lauster's (1992) theory, with validity 0.402 - 0.676 and reliability α = 0.907. The intention scale was developed from the theory of Fishbein Ajzen (1975), validity 0.315 – 0.793 and reliability α = 0.896. Data were analyzed using multiple linear regression analysis with the help of the SPSS application. The relationship between insecurity and intention to use social media is significant t-count 11.470, sig. = 0.000 and coefficient 0.227. The relationship between self-confidence and intention to use social media is significant, with a t count of 15.168, sig. = 0.000 and coefficient 0.388. The results of the regression analysis test F = 405.248 table 3.74 and the Sig value. = 0.000 0.05. So, insecurity and self-confidence together have a significant effect on the Intention to Use Social Media. The determination analysis shows that the adjusted R-squared = 0.683. This shows that the variables of insecurity and self-confidence influence 68.3% of Social Media Use Intentions.